Knowledge, attitude and practices regarding oral cancers amongst secondary school students in Lucknow district - Talib, Mohammad; Gupta, Pratibha; Bhardwaj, Pankaj (International Journal Of Community Medicine And Public Health, 2018)
Background: The world at present is heading towards various types of non communicable diseases which are also known as modern epidemics. Oral cancer is the eleventh most common cancer in the world. It accounts for approximately 2.4 percent of all cancers with high incidence rate in developing countries. Globally, it represents an incidence of 3% and 2% of all cancers among men and women respectively. The aim of the study is to assess Knowledge and Practices about oral cancers amongst the students of intermediate college. Methods: Study design was a cross sectional study. Study population was a list of intermediate colleges from Block Kakori was prepared with the help of social workers of the Department of Community Medicine. Two schools from the list were randomly selected by simple random sampling. Study area was at Kakori Block. Study duration was on July 2011- October 2011. Sample size was a total of 180 students were enrolled for the study who were present at the time of data collection. Data was tabulated using Microsoft Excel and analysed giving descriptive information. Results: Tobacco and alcohol are considered most potent causative agents of oral cancer by the majority (91.1% and 74.4%) of the students.51.1% of students considered it a blood disease, 25% of students told that it is infectious. When asked about knowledge regarding signs and symptoms of oral cancer majority (61.7%) of the students told that indigestion or difficulty in swallowing, unusual weight loss/gain (54.4%) and nagging change or hoarseness of voice by 41.1% students. Television emerges as the source of information about cancer for 55.00% students. 11.10% of students admitted to be using tobacco regularly with cigarette/bidi (42.3%) being the most common type of tobacco usage followed by gutka (30.8%). Conclusions: There is very much need of spreading more awareness about cancer and its prevalence. Correlation between oral cancers and tobacco abuse needs to be highlighted. Significant number of students was not having adequate awareness about signs and symptoms of oral cancers.